Potential of Compost Enriched with Bacillus velezensis B-27 and Bacillus cereus RC76 for the Management of Twisted Disease on Shallots - Putri, Novi Hervianti; Wibowo, Arif; Joko, Tri (Universitas Gadjah Mada, 2023)
Shallot (Allium cepa var. aggregatum.) is a horticultural plant that is widely consumed in the world. However, the productivity of shallots in Indonesia is still relatively low, if compared to the actual optimum production potential of shallot. Shallot cultivation in Indonesia often experiences many problems. One of the problems is twisted diseases caused by Fusarium sp. This research aimed to study the effect of the application of organic material enriched with Bacillus in suppressing the development of twisted disease of shallot. This study was arranged in Randomized Complete Block Design (RCBD) with 5 treatments namely (A) compost + Bacillus velezensis isolate B-27, (B) compost + Bacillus cereus isolate RC76, (C) B. velezensis isolate B-27+B. cereus isolate RC76+compost, (D) compost + Trichoderma asperellum and (E) control (compost 1 ton/ha) with 5 replications on glasshouse treatment and 3 replications on field treatment. The results showed that the combination of B. velezensis in compost effectively reduced the incidence of twisted disease, the number of Fusarium spp. colonies, and the number of infected bulbs by Fusarium sp. Besides, the combination of compost with microbial agents showed better results than compost single treatment.